Hanke, Wanda Völkerkundliche Forschungen in Südamerika - Rodrigues, Aryon Dall’Igna (Revista Brasileira de Linguística Antropológica, 2013)
Kulturgeschichtliche Forschungen Band II. Braunschweig: Albert Limbach Verlag, 1964. 195 pp., references, 101 figures and plates. DM 32.